Charisma and Moral Reasoning - Jessica Flanigan (Religions, 2013)
Charisma is morally problematic insofar as it replaces followers’ capacity to engage in genuine moral reasoning. When followers defer to charismatic leaders and act in ways that are morally wrong they are not only blameworthy for wrongdoing but for failing in their deliberative obligations. Even when followers defer to charismatic leaders and do the right thing, their action is less praiseworthy to the extent that it was the result of charisma rather than moral deliberation. Therefore, effective charismatic leadership reliably undermines the praiseworthiness and amplifies the blameworthiness of follower’s actions.